2003
DOI: 10.1038/sj.cgt.7700663
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent delivery of tumor antigens and activation signals to dendritic cells by irradiated CD40 ligand-transfected tumor cells resulted in efficient activation of specific CD8+ T cells

Abstract: To improve the efficacy of tumor cell-based and dendritic cell (DC)-based cancer vaccines, this study explored the potential of a new cancer vaccine strategy, that is, the use of CD40 ligand-transfected tumor (CD40L-tumor) cells to simultaneously deliver both tumor-derived antigens (Ag) and maturation stimuli to DCs. Materials from frozen/thawed or irradiated human tumor cells, with or without surface CD40L, were internalized efficiently by immature DCs after coincubation. However, during the internalization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…The generation of CD40L-transfected B16F1 tumor cells and their ability to stimulate maturation of DCs have been described previously. 16 For lung metastasis model, mice were immunized with PBS alone, or MIP-tumor vaccine followed by DC vaccine either at different sides of the flank or at the same site on one flank. They were boosted once 2 weeks later with the same protocol.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of CD40L-transfected B16F1 tumor cells and their ability to stimulate maturation of DCs have been described previously. 16 For lung metastasis model, mice were immunized with PBS alone, or MIP-tumor vaccine followed by DC vaccine either at different sides of the flank or at the same site on one flank. They were boosted once 2 weeks later with the same protocol.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…16,23 To increase the purity of BM-derived DCs (BMDCs), cells after GM-CSF/IL-4 culture were enriched by density gradient centrifugation with 80% Ficoll-Paque (Amersham Pharmacia Biotech, Uppsala, Sweden) and cells in the interface were collected as the source of BMDCs. The resulting cells were subjected to flow cytometry analysis and at least 85% of cells were gated based on forward scatter/side scatter setting to detect the expression of various cell markers.…”
Section: Bone Marrow-derived DCmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAbs targeting CD40 represent an attractive therapeutic strategy for a variety of carcinomas. (6)(7)(8)(9)(10) Although MAbs have held great promise for the treatment of human disease such as cancer, viral infection, and autoimmune disorders, the major impediments in murine MAb have been the immune response against murine immunoglobulins and insufficient activation of human effector function. These problems have been overcome using genetic engineering techniques to produce humanized antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, activation of DCs through CD40/CD40L signaling allows DCs to crosspresent exogenous antigen and thus cross-prime CD8 ϩ cytotoxic T cells without CD4 ϩ T-helper cells (51). CD40L has been shown to improve immunogenicity in several therapeutic cancer (40,58) and prophylactic vaccine (20,46) studies. Skountzou et al demonstrated that incorporating CD40L into an SIV virus-like particle enhances humoral and cellular immune responses (61).…”
mentioning
confidence: 99%